1987
DOI: 10.1042/cs0730645
|View full text |Cite
|
Sign up to set email alerts
|

Lithium clearance in man: Effects of dietary salt intake, acute changes in extracellular fluid volume, amiloride and frusemide

Abstract: 1. The effects of amiloride and frusemide on lithium clearance were studied during changes in dietary sodium chloride intake and during infusion of 0.9% NaCl in normal human volunteers. 2. Lithium and fractional lithium clearances were less on the low than on the high salt diet. Values for the medium salt diet were intermediate. Acute extracellular fluid volume expansion with 0.9% NaCl infusion and extracellular fluid volume contraction 3-4 h after intravenous frusemide caused lithium and fractional lithium cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…15 However, Weder 15 measured lithium excretion in subjects with a mean basal fractional sodium excretion of around 0.6%. Since some lithium reabsorption has been demonstrated to occur beyond the proximal tubule in sodium-restricted animals 17 -18 and in humans, 19 lithium excretion may be of limited importance in estimating proximal tubular reabsorption under such experimental conditions. The high sodium intake used in the present study, which ensured a basal fractional sodium excretion of 1.2%, should prevent this confounding factor in estimating proximal tubular reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, Weder 15 measured lithium excretion in subjects with a mean basal fractional sodium excretion of around 0.6%. Since some lithium reabsorption has been demonstrated to occur beyond the proximal tubule in sodium-restricted animals 17 -18 and in humans, 19 lithium excretion may be of limited importance in estimating proximal tubular reabsorption under such experimental conditions. The high sodium intake used in the present study, which ensured a basal fractional sodium excretion of 1.2%, should prevent this confounding factor in estimating proximal tubular reabsorption.…”
Section: Discussionmentioning
confidence: 99%
“…The use of lithium clearance as an index of proximal tubular outflow to the thin descending limp of Henle relies on the assumptions that lithium is reabsorbed in parallel with sodium and water in the proximal tubules, but not reabsorbed or secreted in the distal tubules [9]. Based on direct measurements by in vivo micropuncture techniques in rats [10,17] and indirect evidence obtained by diuretic drug effect studies in man [9,18,19], it is now generally agreed that the lithium clearance method provides a reasonable, whole kidney' measure of end-proximal volume delivery in man under normal physiological conditions [20]. Recently, the lithium test doses used in clearance studies similar to the present one were shown to increase baseline sodium excretion on the study day, but the subsequent response to dopamine remained unchanged [21].…”
Section: Methodsmentioning
confidence: 99%
“…Later studies have consistently shown that loop diuretics increase CL, and FEL, and the lack of effect of loop diuretics on CLI in the study by Thomsen & Schou (1968) has been ascribed to the long urine collection period (7 hours). Thus, furosemide produces substantial increases in CLI and FEL, in both rats (Steele et al 1976;Thomsen & Leyssac 1986a;Christensen et al 1986Christensen et al , 1987Kirchner 1987;Shirley et al 1992;Fransen et al 1993; IV, VI) and humans (Steele et al 1975;Atherton et al 1987Atherton et al & 1988Rombola et al 1987;Sjostrom 1988;Andreasen et al 1989;Shalmi et a1 1990a;Beutler et al 1990). Similar increases in CLI and FEL, have been reported with bumetanide Staalsen & Steiness 1990;Unwin et al 1994), ethacrynic acid , and the stereoisomer 1-ozolinone (Shalmi et al 1990b).…”
Section: Lithium Clearance As a Marker For Proximal Tubular Na And Wamentioning
confidence: 99%
“…Fransen et al (1992) have confirmed these findings and by free-flow micropuncture technique they demonstrated that amiloride inhibits Li reabsorption at a site beyond the early distal tubule in Na depleted rats. There are no evidence for amiloride-sensitive Li reabsorption during Na restriction in humans (Atherton et al 1987;Boer et al 1988;Bruun et al 1989).…”
Section: Lithium Clearance As a Marker For Proximal Tubular Na And Wamentioning
confidence: 99%